OPTICS: OPTical Ibs Coating for Swiss research - (:unkn) unknown (My University, 2025)
With the project OPTICS (OPTical Ibs Coating for Swiss reserach) that has been largely funded by the Swiss National Science Foundation (SNF), we want to establish a Swiss platform at the University of Neuchatel that provides a complete solution for the design, sample preparation, layer deposition, characterization, and laser evaluation of top-quality IBS coatings. With this machine, we will have a unique possibility to use and develop custom optics for all our research fields, i.e., to fabricate optics that are perfectly adapted to the specific needs of our experiments. This infrastructure will also pave the way for many collaborations, where custom-made high-performance coatings are required that exhibit special properties and which are not commercially available. It includes Swiss research institutes, but also a network of Swiss industries.
Keywords: Optical coatings; Ion-beam Sputtering